Impact of Chemotherapy upon Psychological status of School Age Children with Acute Lymphoblastic Leukemia at Pediatric Teaching Hospitals in Baghdad City - Shukran Khudher Kassar Al-ghzy; Eqbal Ghanim Ali Ma’ala (Institute of Medico-legal Publications Pvt Ltd, 2021)
A descriptive design study was conducted to assess the psychological status of the impact of chemotherapyupon school age children with acute lymphoblastic leukemia in Baghdad city and find out the relationshipbetween Impact of Chemotherapy upon psychological status of school age children with acute lymphoblasticleukaemia and their demographic characteristics like children’s( age ,gender, level of education et a)A non-probability (Purposive) sample of 114 children with ALL under chemotherapy was selected inattending hospital wart out pation and counseling clinic.The results of the present study indicated that impactof chemotherapy upon psychological status of acute lymphoblastic leukemia children were effected atmoderate level, with regard to relationships among impact of chemotherapy upon psychological status andchild’s Socio-demographic characteristics,and no significant association was apperThe study concludes that most of the children with acute lymphoblastic leukemia had moderate level, andrecommended that Psychosocial support should be provided to school age children and their parent’s tofacilitate their coping with disease and its treatment. Establishment of counseling clinic especially fortreatment of children with acute lymphoblastic leukemia, to maintain care, reduce the anxiety, and theirconsequently.